Evaluation of the association between the AC3 genetic polymorphisms and obesity in a Chinese Han population. - Hairu Wang (Public Library of Science (PLoS), 2010)
Background AC3 is one of adenylyl cyclase isoforms involved in cAMP and insulin signaling pathway. Recent reports have demonstrated that the AC3 genetic polymorphisms are associated with obesity in a Swedish population. AC3 knock out mice exhibit obese when they age. These findings suggest that AC3 plays an important role in the regulation of body weight. Methodology/principal findings In the present study, we evaluated the association between the AC3 genetic polymorphisms and obesity in a Han Chinese population. A total of 2580 adults, including 1490 lean (BMI = 18.5-23.9), 677 overweight (BMI 24.0-27.9) and 413 obese (BMI ≥28.0) subjects were genotyped for 5 TagSNPs in the AC3 gene. Single maker association analyses indicated that SNP rs753529 was significantly associated with BMI in obese subjects (P = 0.022, OR = 0.775 95%CI = 0.623-0.963), but not in overweight subjects (P = 0.818). Multiple maker association analyses showed that the haplotype (G-G-G) constructed with SNPs rs1127568, rs7604576 and rs753529 was significantly associated with obesity (P = 0.029). Further genotyping of SNP rs753529 in 816 children, including 361 overweight subjects (BMI>P(80)) and 455 controls (BMI = P(20-50)) were performed, and no significant association with BMI was found. All tests were adjusted for age, sex, physical activity index, household income and/or diet expenses. Conclusions The present study provides replication evidence that the AC3 genetic polymorphisms are associated with decreased risk of obesity among adults but not in children in a Chinese Han population. The data also suggest that the AC3 genetic effects on BMI may have interaction with the factors related to ageing and environment.